2020
DOI: 10.7759/cureus.10869
|View full text |Cite
|
Sign up to set email alerts
|

Use of Tocilizumab in COVID-19: A Systematic Review and Meta-Analysis of Current Evidence

Abstract: Background and objectives A flare-up in coronavirus disease 2019 (COVID-19) cases threatens the health of people, and though there is no proven pharmacological treatment, many analytical studies have suggested that interleukin-6 (IL-6) levels are elevated in cases of severe COVID-19 and that the anti-IL-6 biologic agent tocilizumab may be beneficial. This is a critical review of studies aiming to assess the safety and efficacy of tocilizumab as compared to the standard regimen in patients with COVID-19. Materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 29 publications
2
27
0
1
Order By: Relevance
“…Similar results were obtained by previous meta-analysis studies on the effect of tocilizumab treatment on the mortality risk of COVID-19 patients. Khan et al [ 87 ], Rubio-Rivas et al [ 88 ], and Kotak et al [ 89 ] reported RRs [95%CIs] of 0.83 [0.72, 0.96], 0.73 [0.57, 0.93], and 0.56 [0.34, 0.92], respectively, and Zhao et al [ 90 ] and Sarfraz et al [ 91 ] reported odds ratios [95%CIs] of 0.44 [0.36, 0.55] and 0.42 [0.26, 0.69], respectively, with tocilizumab treatment compared with SOC. Despite the promising results in these meta-analysis studies, none of the four published RCTs found a significant beneficial effect on mortality rates for tocilizumab in COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar results were obtained by previous meta-analysis studies on the effect of tocilizumab treatment on the mortality risk of COVID-19 patients. Khan et al [ 87 ], Rubio-Rivas et al [ 88 ], and Kotak et al [ 89 ] reported RRs [95%CIs] of 0.83 [0.72, 0.96], 0.73 [0.57, 0.93], and 0.56 [0.34, 0.92], respectively, and Zhao et al [ 90 ] and Sarfraz et al [ 91 ] reported odds ratios [95%CIs] of 0.44 [0.36, 0.55] and 0.42 [0.26, 0.69], respectively, with tocilizumab treatment compared with SOC. Despite the promising results in these meta-analysis studies, none of the four published RCTs found a significant beneficial effect on mortality rates for tocilizumab in COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Tleyjeh et al [ 92 ] in the meta-analysis of four RCTs reported a pooled RR [95%CI] of 0.71 [0.52, 0.96] for the effect of tocilizumab on mechanical ventilation. Similarly, Kotak et al [ 89 ] demonstrated a lower risk of the need for intubation with a RR [95%CI] of 0.34 [0.12, 0.99]; and Aziz et al [ 93 ] reported lower rates of mechanical ventilation with a risk difference [95%CI] of −0.11 [−0.19, −0.02] in tocilizumab patients. In a recent retrospective study, Salvati et al [ 94 ] found improved alveolar-arterial oxygen gradient and pulmonary vascular radiologic score in severe COVID-19 patients 1 week after tocilizumab treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In six recently published systematic reviews and meta-analyses, the effects of tocilizumab on mortality in patients with severe COVID-19 were not consistent. In four studies, tocilizumab treatment significantly reduced the mortality rate [ 155 156 157 158 ], while opposite findings were observed in two other studies [ 159 160 ].…”
Section: Resultsmentioning
confidence: 98%
“…There were no TCZ -linked complications or illness deterioration (Zhanga et al 2020) TCZ increases the risk of cardiovascular disease (Zhanga et al 2020) TCZ might cause some adverse effects including hepatic damage, neutropenia, thrombocytopenia, or serious secondary infection (Zhangb et al 2020;Kotak et al 2020) Remdesivir (RDV) (A prodrug of an adenosine analogue) RDV is a broad-spectrum antiviral agent and a potent inhibitor of SARS-CoV-2 replication in nasal and bronchial airway epithelial cells (Doggrell 2020) RDV decreases the recovery-time in COVID-19 patients and currently is the first approved anti-viral drug against COVID-19 (Beigel et al 2020) RDV might cause some side effects such as the elevation in hepatic enzyme levels and diarrhea (Grein et al 2020) The poor oral-bioavailability of RDV hindered its prophylactic use (Malin et al 2020) Lopinavir/ritonavir (LPVr) (a protease inhibitor) LPV/r plays an important role in the "early stage i.e. initial 7-10 days" clinical outcome (Yao et al 2020 re-emergence of viral outbreaks, knowing that the vaccines require pre-clinical trials and about 10 months for approval and commercialization.…”
Section: Consmentioning
confidence: 99%